EU engagement with Africa on migration: a change of approach required - Clare Castillejo (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Migration was an important issue at the November African Union (AU)-European Union (EU) summit. While the tone of discussion was somewhat improved on that of recent years, divisions between the two continents remain great. Europe and Africa still have fundamentally different positions in relation to migration, with the EU and many European member states prioritising prevention and return, while African governments focus more on remittances and legal migration opportunities. However, Europe's current approach does not acknowledge these differing interests and instead seeks to impose its own agenda in ways that threaten to undermine important African ambitions. In recent years, the EU has launched initiatives aimed at curbing migration from Africa that have caused significant controversy, notably the EU Emergency Trust Fund for Africa (EUTF) and the Migration Partnership Framework (MPF). These initiatives suffer from a number of weaknesses. The EUTF is based on the flawed premise that development assistance can prevent migration. It diverts aid to migration goals, and its projects often do not comply with development principles such as transparency, ownership and alignment. Meanwhile, the MPF seeks to use positive and negative incentives across a range of external action areas to encourage partners to cooperate with the EU's migration goals – primarily on prevention and return. So far, results have been limited and it has soured relations with some partner countries. The case of Ethiopia illustrates the limitations of the EU's current approach. The country is an important regional player on migration and refugee issues and has been largely constructive in multilateral migration processes, such as Khartoum and Valetta. While Ethiopia is an MPF priority country and a recipient of large amounts of EUTF funding, the goals of the EU and Ethiopia on migration have not been aligned. The EU is frustrated that Ethiopia has not cooperated on returns, while Ethiopia is disappointed that the EU has offered little in terms of legal migration and that EUTF funding has led to multiple, uncoordinated projects that are disconnected from local priorities and are implemented by outsiders. It is clear that the EU needs to change its approach to migration in Africa, beginning with the recognition that Europe will need African migration in years to come. The EU should explore how Africa and Europe can work together to foster intra-African movement that supports Africa's economic growth, to ensure protection for refugees and vulnerable migrants, and to allow both continents to benefit from safe and orderly African labour migration to Europe. It should also move from attempting to address “root causes” of migration with short-term development funds, to examining how Europe could readjust its trade and investment policy in Africa to create more decent jobs and opportunities. Importantly, the EU must continue to press African governments to live up to their responsibilities to provide a decent life for citizens so they do not have to migrate in such large numbers and insecure circumstances. Critically, the EU must be honest about conflicting interests and positions among its own member states and work towards effective common migration and asylum systems. However, such a change in approach requires European leaders to shift the current political discourse around migration to a more constructive one.
Keywords: 330; Flucht und Migration